The Influence Of Parenting Model Toward Juvenile Delinquency And Its Prevention In West Sumatera - Nova, Efren (UI Scholars Hub, 2017)
This research was conducted with legal research methods that can be revealed how the law was perceived and implemented by the community through research Juridical Sociological including reviewing legal issue s as an integral part of the community or research approach which emphasizes the legal aspects with regard to the subject to be discussed, is associated with the fact in the field. The purpose of this study was to determine the extent of the influence and the role of parents in caring and educating children through parenting models that cause juvenile delinquency, as well as the effortsthe parents' role in the juvenile delinquency reduction. Object of this study includes elementary school students and junior high school students as well as High School of state or private school at four Regency or City in West Sumatra. The Results of research shows that the influence of parents' parenting models to juvenile delinquency is very influential. The role of parents is very necessary in the prevention of juvenile delinquency by changing the model of parenting applied